Peranan Perilaku, Kebiasaan dan Dukungan Tokoh Masyarakat terhadap Kepemilikan Jamban Sehat di Pesisir Kampung Bugis Kota Tanjungpinang - Kholilah Samosir; Fajar Surya Ramadhan (Poltekkes Kemenkes Yogyakarta, 2020)
One of the problems of sanitation development in Indonesia is about of socio-cultural challenges, one of which is the behavior of some people who are accustomed to open defecation. The pur-pose of this study was to find out the role of behavior, habits and support of community leaders on the ownership of healthy latrines in the coastal area of Kampung Bugis in Tanjungpinang City, by conducting an analytic observational research with cross sectional design, i.e. to study the correlation dynamics between risk factors and the effects, by observing or collecting data at the same time. The study population were 372 householders in Kampung Bugis, and as the sample was 193 householder. The data were analyzed by chi-square test at 0,05 significance level. The study results indicate that among the factors, significant role is showed by habits (p<0,001), and non-significant role is showed by knowledge (p=0,788), attitude (p=0,092) and support from community leader (p=1,000). Based on the study results, all relevant parties are advised to sup-port the people of Kampung Bugis, so that they can possess healthy latrines that meet health re-quirements and is also proper to use.